BDNF Promoter Methylation Associated with Suicidal Ideation in Patients with Breast Cancer*. (January 2015) - Kim, Jae-Min; Kang, Hee-Ju; Kim, Seon-Young; Kim, Sung-Wan; Shin, Il-Seon; Kim, Hye-Ran; Park, Min-Ho; Shin, Myung-Geun; Yoon, Jung-Han; Yoon, Jin-Sang
Objective: Brain-derived neurotrophic factor (BDNF) has been considered a risk factor for suicidality. BDNF secretion is influenced by epigenetic (DNA methylation) and genetic (val66met polymorphism) profiles. We aimed to investigate the independent effects of BDNF promoter methylation status on suicidal ideation as well as the effects of its interaction with the val66met polymorphism in patients with breast cancer. Methods: A total of279 patients with breast cancer were evaluated 1 week after breast surgery, and 244 (87%) were followed up 1 year later. Suicidal ideation was identified using the item addressing suicidal thoughts on the Beck Depression Inventory. The independent effects of BDNF methylation status on suicidal ideation at two points was investigated using multivariable logistic regression models. The two-way interactive effects of BDNF methylation status and the val66met polymorphism on suicidal ideation were also estimated using the same models. Results: Increased BDNF methylation was significantly associated with suicidal ideation and depression 1 year after breast surgery, and this association was independent of potential covariates, including previous depression, current depressive symptoms, and BDNF genotype. No significant methylation-genotype interactions were found. Conclusions: The BDNF hypothesis and the epigenetic origin of suicidality in patients with breast cancer were supported. BDNF gene methylation status may be a biological marker for suicidality in patients with breast cancer.